THE CORRELATION OF ENDOSCOPIC AND ULTRASONOGRAPHIC FINDINGS IN PATIENTS WITH PORTAL HYPERTENSION - Osman ONAT; Selami SERHATLIOĞLU; Ali DEMİR; Emir DÖNDER; Oğuz AYHAN; Reşat ÖZERCAN; Ahmet YILDIRIM (Turkish Journal of Gastroenterology, 2020)
-